Pendampingan Sertifikasi Halal Produk UMKM di Desa Pomahan Kecamatan Pulung Kabupaten Ponorogo - Nur Ikhsan; Nanik Setyowati (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze a strategy for supporting halal certification among SMEs (Small and Medium-sized Enterprises) with a focus on increasing product sales. The approach of Digital Transformation ABCD is employed within the framework of qualitative methodology to evaluate SMEs in the context of halal certification. Within the ABCD approach, this research investigates how SMEs facilitate access to information, convey the value of halal products, engage with the community, and integrate halal information. The results of this study provide practical guidance for SMEs in the process of halal certification support. The objective is to enhance consumer trust and stimulate business growth for SMEs within the context of halal certification. It is expected that these findings will aid SMEs in understanding the necessary steps to obtain halal certification and effectively communicate about it to consumers through their digital platforms. In conclusion, an approach that supports halal certification with a focus on the values of halal and effective communication has the potential to assist SMEs in building consumer confidence and thriving in the market associated with halal certification.